Analisis Sektor Unggulan yang Ada di Kabupaten Mojokerto Jawa Timur - Irmansyah, Maulana (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
This study aims to determine the leading sectors and sectors that must be prioritized in Mojokerto Regency. This study uses secondary data from Gross Regional Domestic Product (GRDP) of Mojokerto Regency and East Java Province in 2015-2016. The analytical tools used in this study are: 1). Location Quotient Analysis (LQ), 2) Dynamiq Location Quotient Analysis (DLQ), 3) Shift-Share Analysis and 4) Klassen Typology. The results of the analysis by sector shows that the sector which is the leading sector in Mojokerto Regency with criteria classified as the base and competitive sector is the manufacturing sector. For the sectors that must be prioritized in Mojokerto Regency are the manufacturing and real estate sectors.